Recurrent Artery of Heubner Aneurysm Masquerading as Caudate Hemorrhage without Subarachnoid Hemorrhage in Moyamoya Disease: A Case Report and Literature Review - Fu, Chao; Jiang, Peng; Zhao, Yang; Li, Youxiang (Current Medical Imaging, 2022)
Background: Clinically, the recurrent artery of the Heubner (RAH) aneurysm is extremely rare, commonly presents with subarachnoid hemorrhage (SAH). Case Report: A 73-year-old man with a known moyamoya disease was presented as caudate hemorrhage attributable to an incidental flow aneurysm distal on the right RAH, which was managed conservatively after an unsuccessful endovascular attempt. Unfortunately, the patient died five weeks after hospital discharge because of the re-rupture of the aneurysm. To the best of our knowledge, the RAH aneurysm manifesting as caudate hemorrhage without SAH has not previously been reported. Conclusion: This case highlights that the RAH aneurysm masquerading as caudate hemorrhage without SAH is exceedingly rare but can be encountered, representing a diagnostic and therapeutic challenge, and should be considered in the differential diagnosis. Moreover, early identifying and then eliminating such vascular anomaly if possible is of importance to prevent fatal hemorrhage.
Keywords: Recurrent artery of heubner